Markov processes in modeling land use and land cover changes in sintra-cascais, portugal (2009)
In this article the process of land use and land cover change (LUCC) is investigated using remote sensing and Markov chains for the municipalities of Sintra and Cascais (Portugal) between years 1989 and 2000. The role of the Natural Park of Sintra-Cascais (PNSC) in LUCC dynamics is evaluated. Results show that, inside PNSC, present LUCC depends on the immediate past land use and land cover following a Markovian behavior. Outside PNSC, LUCC change is random and does not follow a Markovian process. Estimates of LUCC for year 2006 are presented for the area inside the PNSC. These results reinforce the role of the PNSC as an indispensable tool for preserving LUCC stability and to guarantee its functions.